Answer:
[tex]LCM=65k^3(k+1)^2(k+4)[/tex]
Step-by-step explanation:
We are given the following:
[tex]13k^2 + 26k +13[/tex]
[tex]5k^5 + 25k^4+20k^3[/tex]
We can factor the given polynomial in the following manner.
[tex]13k^2 + 26k +13\\= 13(k^2 + 2k +1)\\=13(k+1)^2[/tex]
[tex]5k^5 + 25k^4+20k^3\\=5k^3(k^2 + 5k + 4)\\=5k^3(k\left(k+1\right)+4\left(k+1\right))\\=5k^3(k+1)(k+4)[/tex]
Thus, the common factors of the both polynomials are:
(k+1)
Thus, the LCM of both the polynomials is
[tex]LCM= (k+1)\times 13(k+1)\times 5k^3(k+4)\\=65k^3(k+1)^2(k+4)[/tex]